Edible seaweeds sold in the local public markets in Tawi-Tawi, Philippines - Dumilag, Richard V. (2019)
Documenting local knowledge regarding the identity and use of wild resources in rural communities is a pressing concern because such knowledge is likely disappearing into oblivion. As easily perceived, the large crowds in public markets provide opportunities for the exchange of local resources. Tawi-Tawi is one of the rural areas in the Philippines for which a list of seaweed species sold in the local marketplace has not been reported to date. Here, a survey of Tawi-Tawi public markets resulted in a list of seven commercialized seaweed species ? namely Caulerpa lentillifera, Caulerpa cf. macrodisca ecad corynephora, Caulerpa cf. racemosa, Eucheuma denticulatum, Kappaphycus alvarezii, Kappaphycus striatus, and Solieria robusta. The local name, description, and other key trade information for each seaweed ethnotaxon were provided. This study contributes to filling in data gaps in ethnophycological literature in the Philippines and its value placed on it by various stakeholders. (Author's abstract)